Criminal Policy of the Iraqi Law maker in The Face of Corruption Crimes (مجلة المنصور, 2022)
There is no doubt that the phenomena of corruption has become one of the issues that imposes itself on the local and international level, as it has become a key impediment to community development in various fields. If the traditional concept of crime is usually committed by poor people, disadvantaged individuals, or outlaws groups, the reality today, in the age of globalization, indicates that the crime can be committed by people in authority and those affiliating to them, and political and commercial governing elites. This thing has allowed corruption to be considered criminality of authority wherever and whenever the positions of authority or state bodies and organizations are exploited to achieve personal interest instead of performing its basic role in the interest of general good. For this. We find that the world Bank has focused on the concept of good government and the criminal policy of the following fundamental ideas.First : equality of all citizens in front of the law without partiality.Second: Having equal opportunities of getting benefits from public services.Third : The necessity of holding those who have been selected to rule on behalf of the people accountable for their failures. Hence, we are committed to present the problem of this paper to demonstrate the effectiveness of the criminal and political efficacy pursued by the Iraqi legislature in this kind of crimes? We also like to see if the Penal Code has become incapable of facing situations in the light of changes occurring concerning these kind of criminal patterns related to corruption.